2014
DOI: 10.4081/jae.2014.226
|View full text |Cite
|
Sign up to set email alerts
|

Thin-layer catalytic far-infrared radiation drying and flavour of tomato slices

Abstract: A far-infrared radiation (FIR) catalytic laboratory dryer was designed by us and used to dry tomato. The kinetics of drying of tomato slices with FIR energy was dependent on both the distance from the heat source and the sample thickness. Numerical evaluation of the simplified Fick’s law for Fourier number showed that the effective moisture diffusivity increased from 0.193×10<sup>–9</sup> to 1.893×10<sup>–9</sup> m<sup>2</sup>/s, from 0.059×10<sup>–9</sup> to 2.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 27 publications
9
11
0
Order By: Relevance
“…It was further revealed that as sample thickness increased, the conductive resistance of the sample proliferated, thus leading to reduction of final product temperature (Figure a). The result is in agreement with previous studies such as infrared drying of tomato samples (Abano et al, ), and apple samples (Nowak & Lewicki, ).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…It was further revealed that as sample thickness increased, the conductive resistance of the sample proliferated, thus leading to reduction of final product temperature (Figure a). The result is in agreement with previous studies such as infrared drying of tomato samples (Abano et al, ), and apple samples (Nowak & Lewicki, ).…”
Section: Resultssupporting
confidence: 93%
“…The drying rates displayed the significant difference with different irradiation distances (Figure ), which was similar to result reported by Abano et al () and Nowak and Lewicki () and was contrary to result reported Cao et al (). The different results might be owing to the difference in distances and materials used.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations